Pretranslational regulation of pyruvate dehydrogenase complex subunits in white adipose tissue during the suckling-weaning transition in the rat. - Maury, J (1995)
Total pyruvate dehydrogenase complex activity is low in white adipose tissue during the suckling period and increases markedly at weaning on to a high-carbohydrate diet. This is concomitant with an increase in the E1 alpha, E1 beta and E2 subunit protein concentration and their respective mRNAs, suggesting a pretranslational control of this phenomenon. The most marked change is seen for the E1 alpha subunit (17-fold increase in protein concentration). The changes in pyruvate dehydrogenase complex activity and subunit abundance induced by weaning on to a high-carbohydrate diet are precluded if the animals are weaned on to a high-fat diet, suggesting that the nutritional and/or related hormonal changes rather than a developmental stage are responsible for the observed adipose-tissue pyruvate dehydrogenase complex pattern.